Measuring function in children with chronic pain: Investigating the validity, reliability, and factor structure of the child and parent versions of the Function Disability Inventory (FDI) in the population of children with chronic pain and their parents - Soheila Ghomian; Mohammad Reza Shaeiri Shaeiri; Samira Masoumian; Tahere Malek Zadeh; Neda Nuri (فصلنامه علمی- پژوهشی اصول بهداشت روانی, 2022)
Introduction: This study aimed to investigate the validity, reliability, and factor structure of the child and parent versions of The Function Disability Inventory (FDI) in the children with chronic pain and their parents. Materials and Methods: The sample consists of 112 pairs of children (7-12 years) and parents selected through convenient sampling from child hospitals in Tehran in 2017 to 2018. The Function Disability Inventory (FDI), KIDScreen, Child Behavior Checklist (CBCL), Youth Self Report (YSR), and Visual Analogous Scale (VAS) were implemented. The data were analyzed using Pearson's correlation and exploratory and confirmatory factor analysis were used to obtain the findings. Results: The reliability results of FDI showed that the Cronbach's alpha of the child and parent versions were 0.89 and 0.90, respectively, which indicates high alpha coefficients. Also, many run twice correlations of child and parent versions obtained in a significant and acceptable range (0.53 to 0.93). Also, the convergent and divergent validity of the parent version showed that the parent version has a negative correlation with the quality of life subscales (-0.08 to -0.20) and with the CBCL subscales (0.30 to 0.35) and also the visual similarity scale (0.15), has a positive and significant correlation. The exploratory factor analysis identified four factors in the child's version and three factors in the parent's version, and in the confirmation factor analysis, the fitting of these new factors were confirmed. Conclusion: Function Disability Inventory has proper psychometric features in the population of children with chronic pain and their parents.